When Jackie and Hank met - Fishman, Cathy Goldberg (Marshall Cavendish Children, 2012)
Examines the similarities of two major league baseball players who met for the first time on May 17, 1947: Jackie Robinson, who had to overcome barriers because of his color, and Hank Greenberg, who faced challenges because of his religion.